Relationship between nitrogen functionality and wheat flour dough rheology: Extensional and shear approaches. (December 2022) - Trevisan, Susane; Salimi Khorshidi, Ali; Scanlon, Martin G.
Graphical abstract: Highlights: Wheat grain protein content positively affected by increasing nitrogen fertilizer. Grain protein composition, viz gliadins/glutenins, altered by nitrogen levels. Extensional and shear tests effectively monitor changes in dough rheology. Increased nitrogen applications can produce dough with less elastic character. Potential to balance nitrogen usage to aid optimum dough elasticity/extensibility. Abstract: Nitrogen supplied to wheat crops to increase grain productivity is being scrutinized because of its role in greenhouse gas emissions. Nitrogen affects food quality as well as food security because it increases grain protein content and can change wheat protein composition, both of which affect the rheological properties of dough made from the grain. This review explores the relationship between nitrogen functionality, wheat protein content and the ratio of gliadins to glutenins through critical assessment of recent studies on nitrogen fertilization of wheat. Moreover, by studying how variations in protein content and the gliadins/glutenins ratio affect the shear and extensional rheological properties of the dough, this review elucidates the direct role of nitrogen on wheat flour dough behavior during processing because process operations primarily employ extensional and shear forces. Nitrogen uptake by wheat plants leads to an increase in wheat protein content and changes in the gliadins/glutenins ratio. Confounding factors associated with wheat plant growth and dough preparation make it difficult to definitively separate effects of wheat protein content from effects of wheat protein composition on dough rheology. Nevertheless, in general, higher protein content is associated with larger gliadins/glutenins ratios, resulting in wheat flour doughs that are more extensible.